Pendeteksian Fraudulent Financial Reporting di Lingkungan BUMN: Perspektif Fraud Hexagon Theory - Fransisca, Veronica; Suhartono, Sugi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study aims to analyze the influence of variables such as financial stability, financial targets, external pressure, ineffective monitoring, audit fees, change in director, change in auditor, total accruals, and CEO duality on the risk of fraudulent financial reporting in state-owned enterprises (SOEs). The study is grounded in agency theory, stakeholder theory, and the GONE theory. The research sample consists of 19 SOEs listed on the Indonesia Stock Exchange during the period 2017-2022, with a total of 114 observations. The sampling method used purposive sampling technique, and data analysis was conducted using logistic regression method with SPSS software version 27. The research findings that financial stability and financial targets have a significant positive impact on fraudulent financial reporting, while other variables do not have a significant influence.